2016
DOI: 10.1039/c6cc07678e
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the optoelectronic properties of MoS2 photodetectors through reversible noncovalent functionalization

Abstract: We present an easy drop-casting based functionalization of MoS2-based photodetectors that results in an enhancement of the photoresponse of about four orders of magnitude, reaching responsivities up to 100 A·W -1 . The functionalization is technologically trivial, air-stable, fully reversible and reproducible, and opens the door to the combination of 2D-materials with molecular dyes for the development of high performance photodetectors.Among the novel two-dimensional (2D) materials, 1-8 transition metal dicha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 53 publications
(71 reference statements)
1
31
0
1
Order By: Relevance
“…[40] The photogenerated chargesw ere trapped into localizeds tates within the band gap of MoS 2 and found to quencht he exciton recombination, hence resulting to photoconductivity increment, photogating effect.I na ddition, the widely used organic dye Rhodamine 6G was found to enhance the photogenerated current by an order of magnitude in devices in which the dye was spin-coated onto mechanicallye xfoliated MoS 2 monolayers. The organic dyes can be easily drop-casted onto MoS 2 nanosheets and stabilizedb yw eak electrostatic forces in ar eversible non-destructive manner.T hese electron-donating dyes increaset he ndoping of mechanicallye xfoliated nanosheets and enhance the photocurrentb yf our orders of magnitude at ambient conditions.…”
Section: Noncovalent Surfacef Unctionalization Of Mos 2 Nanosheets Wimentioning
confidence: 99%
See 1 more Smart Citation
“…[40] The photogenerated chargesw ere trapped into localizeds tates within the band gap of MoS 2 and found to quencht he exciton recombination, hence resulting to photoconductivity increment, photogating effect.I na ddition, the widely used organic dye Rhodamine 6G was found to enhance the photogenerated current by an order of magnitude in devices in which the dye was spin-coated onto mechanicallye xfoliated MoS 2 monolayers. The organic dyes can be easily drop-casted onto MoS 2 nanosheets and stabilizedb yw eak electrostatic forces in ar eversible non-destructive manner.T hese electron-donating dyes increaset he ndoping of mechanicallye xfoliated nanosheets and enhance the photocurrentb yf our orders of magnitude at ambient conditions.…”
Section: Noncovalent Surfacef Unctionalization Of Mos 2 Nanosheets Wimentioning
confidence: 99%
“…The organic dyes can be easily drop-casted onto MoS 2 nanosheets and stabilizedb yw eak electrostatic forces in ar eversible non-destructive manner.T hese electron-donating dyes increaset he ndoping of mechanicallye xfoliated nanosheets and enhance the photocurrentb yf our orders of magnitude at ambient conditions. [40] The photogenerated chargesw ere trapped into localizeds tates within the band gap of MoS 2 and found to quencht he exciton recombination, hence resulting to photoconductivity increment, photogating effect.I na ddition, the widely used organic dye Rhodamine 6G was found to enhance the photogenerated current by an order of magnitude in devices in which the dye was spin-coated onto mechanicallye xfoliated MoS 2 monolayers. Electronsw ere transferred from the photoexcited sensitizer to MoS 2 and the hybrids found to be photoresponsive in ab road spectralr ange from 405 to 980 nm, demonstrating the occurrenceo fp hotoinduced charge-transfer phenomena at the interface.…”
Section: Noncovalent Surfacef Unctionalization Of Mos 2 Nanosheets Wimentioning
confidence: 99%
“…Decoration of TMDCs with molecular fragments via noncovalent approaches, mostly based on dispersion/solvophobic interactions, is relatively easy and has consequently led the way towards potential applications. For example, selective chemical sensors and enhanced photodetectors have already been described using this strategy. Methods for the covalent modification of TMDCs are much scarcer and nearly exclusively limited to the metallic 1T phase …”
Section: Introductionmentioning
confidence: 99%
“…It is noted that carbon nanotubes were also combined with graphene to form hybrid photodetectors with broadband spectral response (covering 400–1550 nm), a high responsivity of 4100 A W −1 , and a fast response time of 100 µs . Besides graphene, 2D TMDs such as MoS 2 and WS 2 have also been combined with organic materials to achieve hybrid photodetectors . For instance, Yu et al reported dye‐sensitized MoS 2 photodetectors utilizing a single‐layer MoS 2 treated with rhodamine 6G organic dye molecules.…”
Section: D‐based Photodetectorsmentioning
confidence: 99%